2011
DOI: 10.14712/18059694.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

The Ameliorating Effect of Exogenous Melatonin on Urinary Bladder Function in Hyperosmolar Bladder Overactivity and its Influence on the Autonomic Nervous System Activity

Abstract: The pathophysiology of overactive bladder (OAB) is multifactorial. Although, the two pivotal myogenic (alterations in bladder smooth muscle contractility and excitability) and neurogenic (increased or sensitized sensory transmission, abnormalities in spinal and supraspinal control) basis for the OAB development have been proposed (4,8,28). The neurogenic theory explains that the backgrounds for OAB seems to be partially related to alterations in bladder afferent nerve fibres localized within the bladder mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…MLT also decreases hypothalamic CRH levels and inhibit the ACTH-stimulated CORT production in the primate and human adrenal gland (172,(177)(178)(179)(180)(487)(488)(489), thus attenuating the adrenocortical secretory response in acute and chronic stress models (491)(492)(493)(494). With respect to the ANS, MLT entrain disrupted autonomic rhythmicity by inhibiting central sympatho-adreno-medullary (SAM) outflow and shifting autonomic balance in favour of vagal activity (154, [495][496][497][498]. Interestingly, research findings suggest a direct enhancing effect of melatonergic transmission in stimulus processing, memory consolidation, and conditional cued fear extinction, especially under stress (499)(500)(501)(502).…”
Section: Melatonergic Treatmentmentioning
confidence: 99%
“…MLT also decreases hypothalamic CRH levels and inhibit the ACTH-stimulated CORT production in the primate and human adrenal gland (172,(177)(178)(179)(180)(487)(488)(489), thus attenuating the adrenocortical secretory response in acute and chronic stress models (491)(492)(493)(494). With respect to the ANS, MLT entrain disrupted autonomic rhythmicity by inhibiting central sympatho-adreno-medullary (SAM) outflow and shifting autonomic balance in favour of vagal activity (154, [495][496][497][498]. Interestingly, research findings suggest a direct enhancing effect of melatonergic transmission in stimulus processing, memory consolidation, and conditional cued fear extinction, especially under stress (499)(500)(501)(502).…”
Section: Melatonergic Treatmentmentioning
confidence: 99%
“…Melatonin has gradually gained interest as a potential cardioprotective and antihypertensive agent . Apart from its antioxidant and scavenger properties reviewed below and its hypotensive effect, melatonin has been shown to centrally modulate autonomic nervous system (ANS) activity by inhibiting central sympatho‐adreno‐medullary (SAM) outflow and shifting autonomic balance in favor of vagal activity . In human and animal research, melatonin is shown to entrain disrupted autonomic rhythmicity and augment sympathoadrenal rhythm amplitude, reduce heart rate, norepinephrine levels, arousal and startle responsiveness, attenuate both orthostatic baroreflex and mental‐stress‐related sympathetic response and increase overall heart rate variability .…”
Section: Melatonergic Effects On Ptsd‐specific Pathophysiological Stamentioning
confidence: 99%
“…Melatonin administration ameliorates bladder overactivity in the hyperosmolar-induced chronic overactive bladder (OAB) rat model, associated with inhibition of the sympathetic drive. 32 Administration of melatonin restored impaired contractile function in bladder strips derived from aged guinea pigs. 33 Melatonin also attenuates ACh-and KClinduced contractions in isolated bladder strips from guinea pigs.…”
Section: Circadian Rhythms In Sensory Urothelial Functionmentioning
confidence: 98%
“…The results of experimental studies suggest that melatonin can influence bladder function. Melatonin administration ameliorates bladder overactivity in the hyperosmolar‐induced chronic overactive bladder (OAB) rat model, associated with inhibition of the sympathetic drive 32 . Administration of melatonin restored impaired contractile function in bladder strips derived from aged guinea pigs 33 .…”
Section: Melatonin and Bladder Functionsmentioning
confidence: 99%